Validation of pharmacokinetic model for quizartinib quantified by UPLC-MS/MS in patients with FLT3-ITD negative newly diagnosed acute myeloid leukemia - Antonio Solana-Altabella; Carles Iniesta-Navalón; Maria Chovi-Trull; Rebeca Rodriguez-Veiga; Marina Lopez-Nogueroles; David Martínez-Cuadrón; Mayte Gil-Candel; Laura Torres-Miñana; Evelyn Acuña-Cruz; Isabel Cano-Ferri; Blanca Boluda; Irene Navarro-Vicente; et al. (European Journal of Clinical Pharmacology, 2025)
Purpose Quizartinib pharmacokinetics in FLT3-ITD negative acute myeloid leukemia (AML) remain largely unexplored. This study aims to validate a population pharmacokinetics model (popPK) for quizartinib in plasma samples of FLT3-ITD negative AML patients. To do so, an ultra-performance liquid chromatography coupled with tandem mass spectrometry (UPLC-MS/MS) method has been developed and validated for the quantification of quizartinib. Methods Plasma samples were collected from FLT3-ITD negative newly diagnosed AML patients undergoing quizartinib therapy at induction in the QUIWI phase II clinical trial [NCT04107727, PETHEMA group] between March 2020 and February 2022. The UPLC-MS/MS method was developed and validated. A previously described popPK model was validated using external validation techniques and implemented using the software NONMEM v7.5. Results The developed UPLC-MS/MS method demonstrated high accuracy and precision with a linear range of 6 to 200 ng/mL, with relative standard deviation between 3–11 and accuracy of 88–97% from nominal values. The external validation of the quizartinib popPK model showed minimal bias at the population level (MdPE: -9.86%; ME: 0.50 ng/mL, p = 0.964), but moderate imprecision (MdAPE: 32.28%) and suboptimal accuracy (F20: 24.5%; F30: 43.4%). Individual predictions improved performance, with negligible bias (MdPE: -0.50%), acceptable precision (MdAPE: 11.27%), and F20 (64.2%) and F30 (77.4%) exceeding predefined thresholds. Visual predictive checks confirmed adequate prediction of median concentrations, though some deviations occurred at extremes. Conclusion This study presents a replicable UPLC-MS/MS method for the determination of quizartinib in plasma. The validated popPK model can be used to optimize dosing strategies in future clinical studies.